2021
DOI: 10.1016/j.firesaf.2020.103128
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical study of pool fire dynamics in an air-tight compartment focusing on pressure variation

Abstract: The present paper studies the fire-induced pressure evolution in an air-tight compartment. Two cases with different sizes (i.e., 0.3 m × 0.3 m and 0.5 m × 0.5 m) of square methanol pool fire are considered. Repeated tests were performed for each case, leading to a total of four fire experiments. The leakage of the compartment is measured under different pressure conditions in order to obtain the relationship between the leakage and the pressure increase. The pressure inside the compartment reaches peak values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…10b). Similar phenomena have also been recently observed in the air-tight compartment with mechanical ventilation [37,38]. After the oxygen in the compartment is consumed, the combustion in the compartment is suppressed, and the cooling process will make the pressure in the compartment lower than the external ambient pressure.…”
Section: Compartment Fires With a Small Gapsupporting
confidence: 76%
“…10b). Similar phenomena have also been recently observed in the air-tight compartment with mechanical ventilation [37,38]. After the oxygen in the compartment is consumed, the combustion in the compartment is suppressed, and the cooling process will make the pressure in the compartment lower than the external ambient pressure.…”
Section: Compartment Fires With a Small Gapsupporting
confidence: 76%
“…Unlike compartments with sufficiently large openings, the fire-induced pressure can rise substantially in air-tight compartments because of the difficulty in releasing hot combustion products and thermal expansion [10]. Experiments carried out in air-tight compartments have revealed an obvious over-pressure during the fire growth period and an under-pressure during the fire decay period in large scale experimental facilities [3,7,11] as well as in real residential buildings [5,6]. Due to the high fire-induced pressure in the experiment, the building structure can even be destroyed [6].…”
Section: Introductionmentioning
confidence: 99%
“…Although the fire growth exponent in design fires is often given the value of 2, a real fire does not necessarily follow the t-squared correlation. For instance, in experiments conducted with methanol liquid pool fires, a logarithmic fitting curve of mass loss rate is reported [15]. In order to get different shapes of the fire growth and decay periods, the fire growth/decay exponent is altered in test series C. The obtained HRR evolutions and fire-induced pressure variations are depicted in Fig.…”
Section: Influence Of Fire Growth Exponentmentioning
confidence: 99%
“…Existing studies have shown that an over-pressure peak will appear in the growth phase of the fire development and an under-pressure peak is observed in the fire decay period [6,7,15,16].…”
Section: Introductionmentioning
confidence: 99%